Scenario Analysis of Waste Management Service Improvement Based on Projected Waste Generation and Service Capacity in Natar Subdistrict, South Lampung Regency - Hayati Firdaus; Arif Setia Jaya (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
The goal of this study is to analyze the waste generation rate and waste service coverage in Natar District, as well as to determine appropriate service improvement scenarios based on the capacity of the Karang Sari Final Processing Site (FPS). Waste generation and collection data were monitored over a 7 day period in March 2024 according to SNI 19-3964-1995 by recording the number of truck trips and waste volume. The analysis found that the collected waste entering the FPS is 24.19 m³/day, significantly lower than the total projected waste generation in Natar District, which is 57.59 m³/day. This discrepancy results in a low service level of only 42%, falling far below the regional target of 70%. A 10% annual improvement scenario, aligned with national targets, is projected to achieve full coverage by 2029. The study recommends integrating service improvements with community based waste reduction programs and strengthening waste banks to support sustainable waste management and extend the FPS's lifespan.